Productivity, Economics and Nutrient Use Eff iciency of Basmati Rice Varieties and its Impact on Soil Fertility under SRI - Panigrahi, Trinath; Garnayak, L. M.; Ghosh, M.; Bastia, D. K.; Ghosh, D. C. (International Journal of Bio-resource and Stress Management, 2023)
The results of a field experiment conducted at OUAT, Bhubaneswar on basmati rice varieties under system of rice intensification (SRI) showed that the application of organic manure (FYM 15.0 t ha-1) produced high grain yield (4415 kg ha-1), biomass yield (10946 kg ha-1) and NPK removal comparable to those of INM (50% RDF+7.5 ton FYM ha-1), but significantly greater than those of inorganic fertilization (RDF). Organic manuring (OM) and INM recorded higher gross return but RDF paid higher net return. OM also showed greater available NPK contents and NPK balance in soil than those of INM and RDF. The lowest available NPK contents and NPK balance were recorded RDF treated plots. Cultivar Pusa Basmati-1performed significantly better than Geetanjali variety. Crop planted at close spacing (20×20 cm2) increased yield and NPK removal over those of wide spacing (25×25 cm2); but had no effect on available NPK contents and reverse effect on NPK balance in soil. Crop productivity, nutrient removal, nutrient content and nutrient balance in soil did not vary much with 10 and 15-day old seedling. The results suggest growing Pusa Basmati-1 at close spacing (20×20 cm2) with 10 to 15-day old single seedlings with organic manuring or INM practice for higher yield and better nutrient balance in soil.